Alexander's campaigns in Sind and Baluchistan and the siege of the Brahmin town of Harmatelia - Eggermont, Pierre Herman Leonard (Orientalia Lovaniensia analecta, 1975)
In quest of the identification and geographical location of the Brahmin town of Harmatelia, known for Alexander's siege which became a favourite literary theme throughout the Hellenistic age, the author has studied this minor problem within the much wider context of the historico-geographic conditions of Sind and Baluchistan about 500 B.C. - A.D. 25. An interesting feature of this book is the new method the author has developed. His interpretation is based on what he calls the Law of the strings of geographical names, viz. the principle according to which the early geographers listed the toponyms of towns, tribes, and mountains.